Application of the IRAP Method Combined with GIS to Improve Road Safety on New Highway Projects in Algeria - Derras, Abdelhak; Amara, Khaled; Oulha, Ramdane (Periodica Polytechnica Transportation Engineering, 2022)
This article aims to proactively predict high-risk accident areas in a new highway project in terms of its technical and geometric characteristics. The purpose of this study is to provide road project managers with better road safety assessment tools for the vehicle occupant category. The methodology used combines the International Road Assessment Program (IRAP) methodology and the Geographic Information System (GIS). The IRAP program enables the calculation and classification of risks for each 100-meter segment besides their categorization using a star rating; whereas, the GIS is used to map the risks and identify high-risk accident segments. This method was applied to a new highway project of 110 hectometres located in GHAZAOUET in Algeria. The results of the study revealed that this combined method is innovative in more than one way as it is an effective decision-making aid tool for road safety experts. It, therefore, makes it possible to target accident-prone sections in a faster way before carrying out on site road safety inspections. Technically speaking, this study shows that the existence of closely curved radii mixed at traffic speeds exceeding 80 km/h and the presence of road exits are the main factors affecting the safety of vehicle occupants. Speed control; thus, remains one among the cheapest measures to improve safety.